Multiscale modeling of compressive behavior of carbon nanotube/polymer composites - Li, C.; Chou, T.W.
This paper reports a multiscale modeling of the compressive behavior of carbon nanotube/polymer composites. The nanotube is modeled at the atomistic scale, and the matrix deformation is analyzed by the continuum finite element method. The nanotube and polymer matrix are assumed to be bonded by van der Waals interactions at the interface. The stress distributions at the nanotube/polymer interface under isostrain and isostress loading conditions have been examined. The buckling forces of nanotube/polymer composites for different nanotube lengths and diameters are computed. The results indicate that continuous nanotubes can most effectively enhance the composite buckling resistance.
Keywords: CARBON NANOTUBE; NANOCOMPOSITES; MULTISCALE MODELING; BUCKLING